2022
DOI: 10.3390/m1333
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure and Anti-Leukemic Activity of 1,3-Dihydro-1-{1-[4-(4-phenylpyrrolo[1,2-a]quinoxalin-3-yl)benzyl]piperidin-4-yl}-2H-benzimidazol-2-one

Abstract: 1,3-Dihydro-1-{1-[4-(4-phenylpyrrolo[1,2-a]quinoxalin-3-yl)benzyl]piperidin-4-yl}-2H-benzimidazol-2-one has been synthesized through a multi-step pathway starting from commercially available 2-nitroaniline. A structure characterization of this new substituted pyrrolo[1,2-a]quinoxaline compound was achieved by using FT-IR, 1H-NMR, 13C-NMR, X-Ray and HRMS spectral analysis. This new pyrroloquinoxaline derivative shows an interesting cytotoxic potential against several human leukemia cell lines (HL60, K562 and U9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Heterocyclic compounds comprising the benzimidazolone fragment have attracted interest due to their remarkable usefulness in various therapeutic applications. Extensive research has revealed several pharmacological and biological properties associated with these compounds, including antiproliferative (Guillon et al, 2022), antibacterial (Al-Ghulikah et al, 2023;Saber et al, 2020), anticancer (Dimov et al, 2021) and antiviral (Ferro et al, 2017) activities.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Heterocyclic compounds comprising the benzimidazolone fragment have attracted interest due to their remarkable usefulness in various therapeutic applications. Extensive research has revealed several pharmacological and biological properties associated with these compounds, including antiproliferative (Guillon et al, 2022), antibacterial (Al-Ghulikah et al, 2023;Saber et al, 2020), anticancer (Dimov et al, 2021) and antiviral (Ferro et al, 2017) activities.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Benzimidazolone derivatives display diverse pharmacological and biological properties including antiviral (Ferro et al, 2017), antibacterial (Saber et al, 2020;Mentes ¸e et al, 2021), anticancer (Guillon et al, 2022), anti-Alzheimer's (Mo et al, 2020), antifungal (Ibrahim et al, 2021), and antioxidant (Ibrahim et al, 2021) activities. In our ongoing research in this area, we are synthesizing compounds that combine the 1,2,3triazole motif with benzimidazol-2-one derivatives.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Cell proliferation assays were performed using MTS tetrazolium (Cell Titer96 Aqueous; Promega, Charbonnières-les-Bains, France) on the human leukemic cell lines K562, MV4-11, Jurkat and MOLM14 as previously described by our team [16,17,21]. Cells (10 5 ) were plated in quadruplicate into microtiter-plate wells in 100 µL of culture medium with various doses of compounds (1; 5; 10; 20; 50 µM).…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…[1,2]. Thus, many pyrrolo[1,2-a]quinoxaline compounds have been designed, synthesized and described as antipsychotic agents [3], antiviral agents [4], adenosine receptor modulators [5], antituberculosis agents [6,7], antiparasitic [8][9][10][11][12][13][14][15] and anticancer compounds [16][17][18][19][20][21][22]. However, despite the recent and promising development of targeted therapies, there is still a need to discover new cytotoxic molecules for the treatment of human cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation